2014
DOI: 10.5056/jnm14012
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution Impedance Manometry Criteria in the Sitting Position Indicative of Incomplete Bolus Clearance

Abstract: Background/Aims We used high-resolution impedance manometry (HRIM) to determine the length of breaks on the isobaric contour which would predict incomplete bolus clearance in patients in the sitting position. Methods In total, 651 swallows in 71 patients with esophageal symptoms were studied using a solid-state HRIM system in the sitting position. Each swallow was classified as complete or incomplete bolus clearance by impedance criteria and peristaltic integrity was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The high-resolution manometry protocol included 30 seconds without swallows to assess basal esophagogastric junction pressure and morphology, followed by 10 swallows of 5 mL of 0.3% saline solution. 7 …”
Section: Methodsmentioning
confidence: 99%
“…The high-resolution manometry protocol included 30 seconds without swallows to assess basal esophagogastric junction pressure and morphology, followed by 10 swallows of 5 mL of 0.3% saline solution. 7 …”
Section: Methodsmentioning
confidence: 99%
“…Data has shown that head rotation and body position can affect UES, EGJ and bolus clearance. Some investigators have even recommended studying patients in the physiological upright position.…”
Section: Introductionmentioning
confidence: 99%
“…Solid-state HRM can also accurately detect the relationship between LES and CD and facilitate the visualization of the interpretation of LES relaxation. 6,12 Data has shown that head rotation and body position can affect UES, 13 EGJ 14 and bolus clearance 14 . Some investigators 15 have even recommended studying patients in the physiological upright position.…”
Section: Introductionmentioning
confidence: 99%